Cytogenetic aberrations in adult acute lymphoblastic leukemia—A population‐based study. Issue 4 (22nd September 2021) - Bergfelt Lennmyr, Emma; Engvall, Marie; Barbany, Gisela; Fogelstrand, Linda; Rhodin, Hanna; Hallböök, Helene
Abstract: Cytogenetic aberrations are recognized as important prognostic factors in adult acute lymphoblastic leukemia (ALL), but studies seldom include elderly patients. From the population‐based Swedish ALL Registry, we identified 728 patients aged 18–95 years, who were diagnosed with ALL 1997–2015 and had cytogenetic information. Registry data were complemented with original cytogenetic reports. BCR‐ABL1 was the most recurrent aberration, with a frequency of 26%, with additional cytogenetic alterations in 64%. KTM2A rearrangement was the second most frequent aberration found in 7%. Low hypodiploidy‐near triploidy and complex karyotype had negative impact, while t(1;19); TCF3‐PBX1 showed positive impact on overall survival. However, after correction for age only complex karyotype remained significant.